Accounting Treatment of the Risk Management in the Modern Trade Banking Activity - Chehlarov, Ivo (Research Papers, 2005)
The object of the study is the economic characteristics of the financial instruments and the possibility of their usage in the process of active management of the inherent in the modern trade banking activity risk. The analysis is concentrated on the methodological aspects of the accounting treatment of the different strategies for management of interest, currency and credit risk using various financial instruments like options, futures, forwards, swap transactions.